2021
DOI: 10.4103/jfmpc.jfmpc_2157_20
|View full text |Cite
|
Sign up to set email alerts
|

Opinion of primary care physicians regarding prescription of generic drugs

Abstract: Background: Generics are low-cost alternatives of the existing approved branded drugs. The aim of this work was to study knowledge and perception about generic drugs among the doctors practicing in government and private healthcare sectors. Methods: A cross-sectional study was conducted with a prevalidated questionnaire. Physicians working in government and private healthcare sectors were asked to fill the survey form after obtaining written informed consent. Descriptiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Only 8.58% (n=10) of drugs were prescribed by generic name. This may be probably due to substandard quality and low effectiveness of generic drugs in our country [16][17][18]. Generic forms of the prescribed immunosuppressants were cheaper than the branded form, but we have determined the cost of the therapy from the price of the branded/generic name from the central pharmacy of the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Only 8.58% (n=10) of drugs were prescribed by generic name. This may be probably due to substandard quality and low effectiveness of generic drugs in our country [16][17][18]. Generic forms of the prescribed immunosuppressants were cheaper than the branded form, but we have determined the cost of the therapy from the price of the branded/generic name from the central pharmacy of the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible explanation is the degree of patient contact and education each healthcare professional provides. Numerous studies have shown that patients tend to have a preference for branded versions of drugs over generics, 5,6 and may be more familiar with brand names due to their easier pronunciation and the influence of direct-to-patient advertising. This point is supported by our findings related to patient instructions, which are the only note types targeted toward patients and have a significantly higher brand name mention frequency.…”
Section: Author/note Propertiesmentioning
confidence: 99%
“…First, it represents a potential conflict of interest; usage of a particular brand name rather than a generic name, even if the medication is patent-protected, provides free advertising for a particular pharmaceutical company, and tacitly expresses a preference for the brand formulation when a generic version is available. Second, it may perpetuate the perception among patients and clinicians that brand medications are "better" than generics; recent studies suggest that this perception still exists [4][5][6] despite ample evidence to the contrary. 7,8 Third, usage of brand names may change prescribing behaviors when generic alternatives exist, thereby potentially increasing cost of care.…”
Section: Introductionmentioning
confidence: 99%